Answers

2015-10-29T00:20:22+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
X² - 3x + 2 = 0 ------------------(1)
2x² - 5x + 2 = 0 ----------------(2)

Multiply equation (1) by 2, we get
2x² - 6x + 4 = 0 -----------------(3)

subtract equation (3) from (2)
2x² - 5x + 2 = 0
2x² - 6x + 4 = 0
(-)     (+)  (-)       
        x - 2 = 0
⇒ x = 2

The common root is 2.
1 5 1
The Brainliest Answer!
2015-10-29T00:21:25+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
x² - 3x + 2 = 0
⇒ x² - 2x - x + 2 = 0
⇒ x(x - 2) -1(x - 2) = 0
⇒ (x - 2)(x - 1) = 0
⇒ x = 2 or 1

2x² - 5x + 2 = 0

⇒ 2x² - 4x - x + 2 = 0
⇒ 2x(x - 2) -1(x - 2) = 0
⇒ (x - 2)(2x - 1) = 0
⇒ x = 2 or 1/2

So, the common root of the given quadratic equations is 2.

2 5 2
click on thanks button above ; select best answer